Factor analysis of the development of tourism business in Kazakhstan - A. T. Tleuberdinova; Z. M. Shayekina; D. M. Salauatova; S. Pratt (Экономика: стратегия и практика)
Tourism has become an important sector that affects the development of the country’s economy. The main benefits of tourism are income generation and job creation. For many regions and countries, this is the most important source of wealth. The driving force behind the development of the tourism industry is the activities of entrepreneurs. Through the analysis of available secondary data, this research aims to identify the most important factors influencing tourism entrepreneurship in Kazakhstan.Given the importance of market development and entrepreneurship for economic growth, this study seeks to understand the relationship between entrepreneurship and other macroeconomic indicators. The desire for a better understanding of entrepreneurship is important because of the special role of entrepreneurship in the development of an innovative economy and the need for more strategic use of limited resources.The aim of the work was to assess the factors of the macroenvironment affecting tourism business in Kazakhstan through regression analysis.The article provides a statistical analysis of the number of active subjects in the tourism sector and identifies the main quantitative factors affecting its development. The result of the study was the identification of significant factors that influence the development of the industry.The scope of the research results is the activity of tourism industry entities: the Ministry of Culture and Sports, Tourism Development Offices, tour operators and travel agents, industry organizations, employees of research institutes. The results of the study can be used in the development of state and regional programs for the development of the tourism industry in Kazakhstan.